Caries excavation : evolution of treating cavitated carious lesions - About, Imad; Bjørndal, Lars 1963-; Blunck, Uwe; Bonifacio, Clarissa; Conrads, Georg; Schwendicke, Falk; Frencken, Joannes Elisabert Fredericus Maria 1950-; Innes, Nicola (Basel : Karger, 2018)
Currently there is no reason, in most cases of cavitated caries lesions, to remove affected tissue. This book presents evidence-based research on the topic and provides assessments of diagnostic devices. It offers new insights into how a dentine carious cavity can be managed by either tissue removal or restoration. Methods for preserving dental tissue are presented and ample evidence highlights the need to seal with a quality restorative material. An update on how to conduct a randomized clinical trial is followed by a chapter on agreed upon terminology for supporting improved communication among oral health professionals around the world. This is a must-read for general practitioners, restorative specialists, dental students, and oral hygienists/therapists.
La función de los autores fue determinada por el catalogador
Keywords: CARIES DENTALES -- TRATAMIENTO; RESTAURACION DENTARIA PERMANENTE